Efficacy of needle-knife combined with etanercept treatment regarding disease activity and hip joint function in ankylosing spondylitis patients with hip joint involvement: A randomized controlled study. Issue 19 (May 2020) - You, Yuquan; Cai, Meimei; Lin, Junsheng; Liu, Lianqun; Chen, Changxian; Wang, Yong; Cai, Yaping
Abstract : Abstract: This study aimed to assess the efficacy of needle-knife (NK) combined with etanercept (NKCE) in attenuating pain, inflammation, disease activity, and improving hip joint function in ankylosing spondylitis (AS) patients with hip joint involvement. Totally, 90 patients with active AS involving unilateral hip joint were enrolled and randomly assigned in 1:1:1 ratio to receive NKCE, NK or conventional drugs (control). The ESR, CRP, hip joint pain Visual Analogue Scale (VAS) score, bath ankylosing spondylitis disease activity index (BASDAI), bath ankylosing spondylitis functional index (BASFI), modified Harris hip score (mHHS), and range of motion (ROM) of affected hip joint were assessed at baseline (W0), after 1-week treatment (W1) and after 24-week treatment (W24). ESR and CRP were decreased in NKCE group compared with NK and control groups, while was not attenuated in NK group compared with control group. Regrading pain and disease activity, NKCE group presented a reduction in hip pain VAS score and BASDAI compared with NK and control groups, and NK group showed a decrease in hip pain VAS score and BASDAI compared with control group. Besides, BASFI was lowered in NKCE and NK groups compared with control group, but similar between NKCE and NK groups. mHHS and hip ROM were raised in NKCE and NK groups compared with control group, but similar between NKCE and NK groups. NKCE decreases hip pain, inflammation, disease activity and improves hip joint function in AS patients with hip joint involvement.